New species and new records of genus Rhyacophila Pictet (Trichoptera: Rhyacophilidae) from Dabie Mountains, east-central China - Qiu, Shuang; Yan, Yunjun (Zootaxa, 2016)
Three new species of Rhyacophila, Rhyacophila longiramata n. sp., Rhyacophila haplostephanodes n. sp., and Rhyacophila brevitergata n. sp., from the Dabie Mountains of east-central China, are described and illustrated. Rhyacophila longiramata n. sp. and R. haplostephanodes n. sp. both are highly specialized, which makes them very difficult to be put in any existing species group. Possible positions for these two species are discussed. Rhyacophila brevitergata n. sp. belongs to the R. nigrocephala Species Group. Rhyacophila spp. from Dabie Mountains are listed.